2004
DOI: 10.1080/09553000410001680332
|View full text |Cite
|
Sign up to set email alerts
|

Cataract in atomic bomb survivors

Abstract: Significant radiation effects were observed in two types of cataracts in A-bomb survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 18 publications
5
95
1
1
Order By: Relevance
“…As for the risk of radiation lens injuries at a low dose, available studies are limited at present, and many of them were conducted on atomic bomb survivors. [2][3][4][5] The beam quality and dose rate differ between the exposure to patients undergoing brain CT and the exposure to the objects in these studies, and the differences will affect the risk. Future risk assessment of radiation lens injuries for diagnostic x-rays is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the risk of radiation lens injuries at a low dose, available studies are limited at present, and many of them were conducted on atomic bomb survivors. [2][3][4][5] The beam quality and dose rate differ between the exposure to patients undergoing brain CT and the exposure to the objects in these studies, and the differences will affect the risk. Future risk assessment of radiation lens injuries for diagnostic x-rays is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of recent studies have supported lower thresholds for radiation-induced lens injuries. [2][3][4][5][6] Some authors have suggested that the risk of cataract increases with increased radiation dose without a threshold. 2,3 Given these data, the ICRP referred to the need for a detailed revaluation of the radiosensitivity of the lens.…”
mentioning
confidence: 99%
“…According to the results of the performed studies, estimation of dose received by the lens markedly varied and in some cases the knowledge of exposure level was not even available as was the case for Chernobyl children [16]. In Otake et al and Minamoto et al [13,14], the studies' main advantage was the use of the eye organ dose which allows an estimation of the dose received by the lens. In Worgul et al [12], uncertainties on the estimated doses remain an important limit of the paper, even if the impact of dose uncertainty on the results was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with other non radiation-induced cataracts would have been welcomed to eliminate potential confounding factors. In contrast, Minamoto's study [14] used a standardized classification to grade cataract and each type of lens opacity was separated during the statistical analysis. In Nakashima's study [15] they also separated the different types of lens opacities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation